The Effect Of Training, Incentive Provision, Work Promotion, And Participation In Policymaking On The Performance Of Nurses - Damanik, Marco Frans Hernandes; Sitanggang, Rido Aliberto; Girsang, Ermi; Manalu, Putranto (UNIVERSITAS PAKUAN, 2019)
Human resources in a hospital are expected to always provide maximum and optimum performance in providing services to their patients. Nurses dominate the number of health officers in a hospital and hold an important role because they serve patients 24 hours. This study aims to determine the effect of training, incentive provision, work promotion, and participation in policymaking on the performance of nurses in Royal Prima Marelan General Hospital. This is a quantitative study with a descriptive-analytic design. The population consisted of all nurse executives in the Royal Prima Marelan General Hospital. Two hundred and twenty-four samples were taken using the total sampling technique. Data were analyzed with univariate, bivariate, and multivariate analysis. Results showed that age, education, and years of service affect the performance of nurses in Royal Prima Marelan General Hospital. However, gender did not affect the performance. Training affected nurse performance with a p-value of 0.05. Work promotion and participation in policymaking also affected the performance of nurses with a p-value of 0.05 on both aspects. Nurses’ characteristics, training, incentive provision, work promotion, and participation in policymaking simultaneously affect the performance of nurses in Royal Prima Marelan General Hospital. The most influential independent variable was participation in policymaking.